Dynamics and Trading Behaviour of Four Domestic Institutional Investors in Indian Stock Markets - SRIVASTAVA, Purwa; VARSHNEY, Sakshi; MAHESHWARI, Taru; SINGH, Neha; RANA, Divya (Theoretical and Practical Research in Economic Fields, 2025)
The stability of financial markets is the need of the hour. The runaway of foreign institutional investors has left Indian markets dry many times. Domestic institutional investors (DII) have rescued stock markets during many turbulence-making events. The study focuses on the Trading strategies of four types of DIIs in Indian stock markets: mutual funds, Insurance companies, Development financial institutions, and banks. A vector autoregressive model is used to study the behavior of Four DII’s (insurance companies, development financial institutions, banks, mutual funds) in Indian stock markets on daily data. The data is studied at three levels Buy Sell and Net. Banks became positive feedback traders whereas mutual funds, insurance companies, and development financial institutions were found as negative feedback traders. These results broke the myth about DII’s as only contrarian traders in the Indian context. The study results reveal the significant impact of purchase and sell done by all the DII’s on stock returns. At the Net investment level, it is Mutual funds and development financial institutions impacting the stock market. Buying done by banks also creates price pressure in the markets. It is the first paper in the Indian context to study the domestic institutional investor's data at the disaggregated level. The daily data is taken from the Securities Exchange Board of India (SEBI) on special requests under the regulatory authority's data-sharing policy. Such a bifurcation study on trading strategies is mostly done in the U.S. and Japan to the best of my knowledge. The research on DII at the bifurcated level may include pension funds, Hedge fund, Venture capital funds, and REITs in future research Regulatory authorities should make policy changes so that Insurance companies, Development financial institutions, mutual funds, and banks can increase their investment corpus in stock markets as their investment is having a positive effect on stock markets. Investor awareness programs against panic selling in mutual funds will benefit investors as they will be able to gain more earnings from their mutual funds’ investments. Insurance awareness programs will not only increase their investment corpus but also make society self-reliant.